ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI RUMAH TANGGA PNS GURU SD DI KECAMATAN KOTAANYAR KABUPATEN PROBOLINGGO - Lestari, Wardiyah Puji (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study aims to determine and analyze the factors that may affect household consumption of Civil Cervant Elementary School Teachers at Kotaanyar District of Probolinggo Regency. Some of factors are used to analyze the consumption household such as respondent income, family member, and husband/wife’s respondent income. This research used multiple linear regression model or OLS (Ordinary Least Square) as the methods of data analysis. 60 respondents are selected to participate in this study. The result of the data analysis shows that the variable respondent income (X1), family members (X2), and husband/wife’s respondent income (X3) are gives positive and significant impact on household consumption of Civil Servant Elemmentary School Teachers at Kotaanyar District of Probolinggo Regency.Keywords: household consumption, respondent income, family members, husband/wife’s